DOCTORAL STUDIES IN THE HOMELAND HIGHER EDUCATION: EXPERIENCE AND PROSPECTS OF THE EUROPEAN DIMENSION - Holovko, Svitlana (Proceedings of National Aviation University, 2017)
Purpose: Ensuring compliance of doctoral training in Ukraine with the European standards is an objective condition for the complete integration of our state into the united educational and scientific environment. In order to ensure the effectiveness of this process, the necessity of research conducted on the European experience as well as the first achievements and difficulties in the national high school, the determining factors, in particular, the state and prospects of the legal area development for the implementation of the new model appears to be urgent. Methods: general and specific scientific (special) methods were used to achieve the research target. Applying the methods of the first group made it possible to outline the tendencies of the doctoral training transformation in European countries and in Ukraine. By means of the comparative legal method, the peculiarities of the development of the normative-legal field of doctoral training in the national high school were analyzed, and the areas of its improvement were determined. Results: The features of development of doctoral training in the European educational space and the prospects of its introduction in the national higher education were considered. The formation of the legal area of doctoral training in Ukraine was argued, and the ways of its improvement were outlined. Exemplified on the National Aviation University, as one of the leading research institutions, the first experience of introducing a European model for training scientific staff is summarized. Discussion: In doctoral training, one of the leading trends is the issue of ensuring the quality of the implementation of curricula of the Doctor of Philosophy, enhancing the autonomy and responsibility of postgraduate students and academic leaders, improving the academic and geographical mobility of scholars, increasing funding for research and enhancing its innovation. In the projection of this issue on the national university education, the problem of the methodology of doctoral training, aimed at the personality of a young scientist as a leading subject of creating new knowledge, implementation and development of normative and legal support of this process, is required.